Ethereum Blockchain in Preserving Integrity of Voting System - Law Yun Tong, Arkayanik; Chuah, Chai Wen (Applied Information Technology And Computer Science, 2021)
Voting is a method for a group of people makes a collective decision individually. It can be done by using paper-based method or voting system. Voting System has been around more than a decade. However, the most used voting method is still paper-based. The reason for this is because the concern of security risk that exist in voting system particularly the integrity of casted vote. With voting system being online, the risk of vote fraud happen increase. Thus, a mechanism to validate the integrity of casted votes is needed. In this project, the underlying technology that is proposed to solve this issue is Blockchain technology. Blockchain is known as immutable ledger that record every transaction that happened in a decentralized manner. The technology provides data integrity because of the nature of chaining each node hash value to each other in chronological order. The methodology for this project is Object-Oriented Analysis and Design (OOAD). The proposed system is developed using Java programming language. Overall, the developed system is able to save the casted vote into the Ethereum blockchain. Thus, the integrity of the casted vote is protected.